2017
DOI: 10.1002/anie.201704832
|View full text |Cite
|
Sign up to set email alerts
|

Highly Fluorescent Pyridinium Betaines for Light Harvesting

Abstract: We report the findings of our experimental and theoretical investigations into the properties of pyridinium enolates and their potential utility in light-harvesting applications, such as in luminescent solar concentrators (LSCs). We present the synthesis, structures, photophysical characterization, and wavefunction-based quantum-chemical studies of five cyclobetaines. The performance of an LSC device incorporating one of these cyclobetaines is shown to be comparable to state-of-the-art devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Respect to the two first classes of compounds, organic dyes are usually less toxic and their optical properties can be modulated by changing portions of the carbon backbone or introducing specific functional groups. Dyes proposed for LSCs applications are coumarins, rhodamines, pyrromethane 580, naphthalimides, perylenebisimides, bipyridines, dicarbocyanins, dicyanomethylenes, oxazines, and phthalocyanines [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Among all these classes, only a very limited number of dyes have resulted in being suitable for LSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Respect to the two first classes of compounds, organic dyes are usually less toxic and their optical properties can be modulated by changing portions of the carbon backbone or introducing specific functional groups. Dyes proposed for LSCs applications are coumarins, rhodamines, pyrromethane 580, naphthalimides, perylenebisimides, bipyridines, dicarbocyanins, dicyanomethylenes, oxazines, and phthalocyanines [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Among all these classes, only a very limited number of dyes have resulted in being suitable for LSCs.…”
Section: Introductionmentioning
confidence: 99%
“…A Monte Carlo ray simulation also suggested that absorbance of the waveguide had significant influence on the performance of large-area LSCs. − The absorbance of PMMA and glass-based waveguides was obtained by measuring the transmittance minus the reflectance, while absorbance of the ideal substrate was set at 0. These absorbance values were used in the simulations.…”
mentioning
confidence: 99%
“…Pyridine is one class of electron-withdrawing aryl ring, and exists widely in nature and other functional compounds. [33][34][35][36][37][38] Electronic characteristics of pyridine can be easily adjusted by N-methylation to make it more electron deficient, or by N-oxide to make it electron-rich, which could be used to study the influence of electronic effect on AIE properties of fluorophores with the same emissive core.…”
Section: Introductionmentioning
confidence: 99%